THE EFFECT OF TIME MANAGEMENT ON WORK FATIGUE OF FIREFIGHTERS AT BALIKPAPAN REFINERY UNIT V - Kisworo, Heru; Sembiring, Edison C; Sugiarto, Sugiarto; Sukwika, Tatan (UNG, 2025)
Work fatigue is a critical challenge for firefighters, particularly in high-risk industries such as oil refineries. The novelty of this study is its focus on environmental and operational context as the main factor influencing firefighter fatigue, rather than traditional time-related aspects. This study analyzes the relationship between work time management including work duration, shift type, weekly workdays, sleep duration, and work location and fatigue levels among firefighters at the Balikpapan Refinery Unit V (RU V). A quantitative cross-sectional design was applied with total sampling of 77 respondents. Data were collected using the Fatigue Assessment Scale (FAS) and analyzed through the Chi-Square test. The majority of respondents experienced mild fatigue (72.7%). Among the five variables examined, only work location showed a significant association with fatigue (p = 0.006). Firefighters assigned to RU V had an 8.2 times higher risk of fatigue than those at the Lawe-Lawe Terminal. Practical recommendations include adopting Fatigue Risk Management System (FRMS)-based scheduling, tailoring work arrangements to site conditions, and implementing regular fatigue monitoring to strengthen firefighter safety and performance.